Implementasi Transformasi Digital pada Pegadaian Syariah: Kajian Terhadap Kesiapan, Hambatan, dan Prospek Pengembangan (Studi Kasus PT. Pegadaian Syariah Cabang Kendari): Implementation of Digital Transformation at Sharia Pawnshops: Study of Readiness, Obstacles and Development Prospects (Case Study of PT. Pegadaian Syariah Kendari Branch) - Salehaman Salehaman; Elsa Giana; Kiki Novita (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2026)
Digital transformation has become a necessity in modern financial services, including Islamic Pawnshop based on Islamic financial principles. This research analyzes the readiness, barriers, and prospects of digital transformation at the Islamic Pawnshop Branch in Kendari City. Using a qualitative approach and case study method, data was obtained through interviews, observations, and internal documentation. Data validity is ensured through triangulation techniques. the results indicate a fairly good readiness in terms of technological infrastructure, availability of digital applications such as gold savings, as well as internal support from management and the Islamic Supervisory Board. Employees have internalized technology through the use of applications, although formal training is still limited. The main obstacles come from external factors, namely resistance from some customers, especially the elderly and housewives, due to low digital literacy and concerns about security. Another challenge is the limited budget to develop secure, user-friendly, and Sharia- compliant applications. Nevertheless, the prospects remain bright with product innovations, national digital collaboration, and digital habituation policies. With increased public education and human resource training, Islamic Pawnshop has the opportunity to become a leading, inclusive, and sustainable digital Islamic financial pioneer.